Blessed, precious mistakes: deconstruction, evolution, and New Atheism in America - Schaefer, D (Springer Science+Business Media Dordrecht, 2014)
This paper explores the ways that Daniel C. Dennett’s bestselling 2006 book Breaking the Spell traffics in a set of distinctly American presumptions about the relationship between religion and science. In this Americanized atheism, religion is presumed to be a set of logically organized propositional beliefs–a misbegotten science in need of correction or elimination. I show that a convergent critique, drawing on both evolutionary theory and deconstruction, highlights the limitations of this approach. This convergence highlights the theme of accident in both pluralist evolutionary biology and continental philosophy of religion. Thematizing accident opens up a new conversational space between a deconstructive approach to religion and postadaptationist evolutionary theory, with implications not only for a philosophical understanding of religion, but for new, postsecular atheisms.